Structure elucidation of colibactin and its DNA cross-links - Xue, Mengzhao; Kim, Chung Sub; Healy, Alan R.; Wernke, Kevin M.; Wang, Zhixun; Frischling, Madeline C.; Shine, Emilee E.; Wang, Weiwei; Herzon, Seth B.; Crawford, Jason M. (Science (American Association for the Advancement of Science), 2019)
Strains of the human gut bacterium Escherichia coli carrying the clb gene cluster produce a secondary metabolite dubbed colibactin and have been provocatively linked to colorectal cancer in some models. Colibactin has been difficult to isolate in full, but pieces of the structure have been worked out, including an electrophilic warhead. Xue et al. found that colibactin contains two conjoined warheads, which is consistent with its ability to alkylate and cross-link DNA. Chemical synthesis and comparison to cell coculture confirm the structure and properties of this unstable and potentially carcinogenic metabolite. Science , this issue p. eaax2685 A DNA cross-linking metabolite from gut microbes is made by joining two precursor units. Colibactin is a complex secondary metabolite produced by some genotoxic gut Escherichia coli strains. The presence of colibactin-producing bacteria correlates with the frequency and severity of colorectal cancer in humans. However, because colibactin has not been isolated or structurally characterized, studying the physiological effects of colibactin-producing bacteria in the human gut has been difficult. We used a combination of genetics, isotope labeling, tandem mass spectrometry, and chemical synthesis to deduce the structure of colibactin. Our structural assignment accounts for all known biosynthetic and cell biology data and suggests roles for the final unaccounted enzymes in the colibactin gene cluster.